PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI AMALAN NILAI-NILAI PANCASILA PADA SISWA KELAS V - Nuriska Jr Nabar; Mujahid Damopolii; Karmila Iskandar (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine whether the Application of Audio Visual Learning Media Can Improve Student Learning Motivation on the Material of the Practice of Pancasila Values ​​in the Subject of Pancasila and Citizenship Education at SDN 17 Limboto. This type of research is classroom action research. The object of this study is to use Audio Visual Learning Media in Canva to improve student learning motivation on the subject of PPKn in Grade V of SDN 17 Limboto. The subjects of this study were 20 fifth grade students at SDN 17 Limboto. The data analysis techniques used in this study were analysis of test results and analysis of observation results. Based on the results of the study, it can be concluded that learning using Audio Visual learning media can improve the quality of PPKn lessons on the material of the Practice of Pancasila Values ​​for grade V of SDN 17 Limboto. Student learning outcomes before the application of Audio Visual learning media have not reached the KKTP. After the application of Audio Visual learning media, student learning outcomes have increased, which can be seen in the increase in completeness in the pre-cycle of 25%, increasing in cycle 1 to 55% and in cycle II increasing to 80%. Thus, student learning outcomes and analysis of observation sheets have increased in a better direction with the application of Audio Visual learning media.